Reinvestigation of Ostreopsis mascarenensis Quod (Dinophyceae, Gonyaulacales) from Réunion Island (SW Indian Ocean): molecular phylogeny and emended description. Issue 2 (3rd March 2020) - Chomérat, Nicolas; Bilien, Gwenaël; Couté, Alain; Quod, Jean-Pascal
ABSTRACT: Ostreopsis mascarenensis is a toxic dinoflagellate described from the Indian Ocean based only on morphology, without molecular data. Morphological features of Ostreopsis have poor taxonomic value, and the addition of genetic data would ensure correct species identification. The present study reinvestigated field samples from Réunion Island and the western Indian Ocean to validate morphological and genetic data of O. mascarenensis from the type locality. A detailed morphological study used light, epifluorescence and scanning electron microscopy, and phylogeny was inferred from sequences of the LSU rDNA (D1–D3 and D8–D10 domains) and ITS–5.8S region obtained from isolated single cells. Morphology mostly agreed with the original description, but we highlight some features that were probably in error in the original description. SEM showed that the epitheca was conspicuously flattened while the hypotheca was convex, which had been previously interpreted as the opposite. Moreover, in contrast with the previous interpretation, the second apical plate was long and narrow, 1.6 to 2 times longer than the apical pore. Phylogenetic analyses showed that O. mascarenensis forms a new lineage among Ostreopsis species, confirming that it is well separated from all other species. Based on these analyses, O. mascarenensis appeared to be related to Ostreopsis fattorussoi and the undescribed species Ostreopsis sp. 3 and sp. 4, but the topologies were not well supported and these relationships remain unclear.